When the game of golf becomes a nuisance / Chris Davies - Davies, Chris (Universiti Teknologi MARA, 2021)
Golf is a popular outdoor sport played in many countries across the world. However, the fact it involves hitting a hard ball considerable distances can create problems if the balls are mishit and stray from the course. When it does, there can be a potential claim in nuisance, with the golf club itself being liable once it becomes aware of the nuisance. Often it is an injunction to prevent the continuation of the nuisance that is sought by the plaintiff, though damages can, and have, been awarded. If there is a problem with balls being mishit off the course, the golf club is required to remedy the situation by putting up barriers, or redesigning the course by, for example, shortening the holes in the area where there is a problem.